Penerapan Aplikasi Wordwall sebagai Media Pembelajaran Interaktif di SMP Budi Murni 1 Medan - Purba, Celine; Sembiring, Apri; Ginting, Angelina; Sidabungke, Aldyan; Sinamo, Suci (Sinesia : Jurnal Pengabdian Masyarakat, 2025)
The application of technology in education is increasingly important to increase student effectiveness and engagement. Wordwall is a digital platform that allows the creation of educational games, quizzes and interactive exercises to strengthen students' understanding of lesson material. In this activity, Wordwall is applied directly in the learning process in class 7 of SMP Budi Murni 1 Medan, where students actively participate in various activities related to the material being taught. The results show that the use of Wordwall can significantly increase student motivation and engagement, as well as strengthen their understanding of the material. Increased participation can be seen from the enthusiasm and activeness of students in answering questions and taking part in educational games provided by this application. By using Wordwall as a learning medium, teachers can provide a more interesting and interactive learning experience. The use of Wordwall has proven effective in supporting the teaching and learning process, and it is hoped that it can continue to be implemented to improve the quality of learning at SMP Budi Murni 1 Medan and in other schools.